Improving marketing performance based on analysis of comparative and competitive advantages: an empirical study on java coffee agroindustry in Jember-Indonesia - Kurniawan, Bagus Putu Yudhia; Halil, Halil; Abdul Razzaq, Abdul Rasid; Jumintono, Jumintono (ExcelingTech, 2020)
This study aims to determine the priority strategies for improving the marketing performance of Java Jember Coffee agroindustry based on an analysis of comparative and competitive advantage. The study was conducted using the census method or a complete calculation involving 15 Java Jember Coffee agroindustry. Data were analyzed with the Policy Analysis Matrix (PAM), the TOWS matrix to formulate alternative strategies, and determine priorities using the Analytical Hierarchy Process (AHP). The results showed that the Java Jember-Indonesia coffee agroindustry has a comparative and competitive advantage. The coefficient indicates this on Domestic Resource Costs (DRC = 0.69) and Personal Cost Ratio (PCR = 0.4), which is smaller than 1.00. Java Coffee Jember-Indonesia's agroindustry position is in cell V with the choice of Strategy to hold and maintain and can be managed through market penetration strategies and product development. The priority strategies implemented to improve the marketing performance of Jember-Indonesia Java Coffee agroindustry are to improve product quality, implement Standard Operating Procedures (SOP), collaborate with suppliers of raw materials, superior Human Resource (HR), product diversification and packaging.